Prosthodontic Rehabilitation and Follow-Up Using Maxillary Complete Conventional Immediate Denture - Yeung C; Leung KCM; Yu OY; Lam WYH; Wong AWY; Chu CH (Dove Medical Press, 2020)
Conson Yeung, Katherine Chiu Man Leung, Ollie Yiru Yu, Walter Yu Hang Lam, Amy Wai Yee Wong, Chun Hung Chu Faculty of Dentistry, The University of Hong Kong, Hong KongCorrespondence: Chun Hung ChuFaculty of Dentistry, The University of Hong Kong, 3B26, Prince Philip Dental Hospital, 34 Hospital Road, Sai Ying Pun, Hong KongTel +852 2859 0287Email chchu@hku.hkAbstract: Despite global efforts to improve individuals’ oral health, a considerable proportion of patients still progress to the stage in which the extractions of all teeth in one arch or both are indicated. An immediate complete denture remains a relatively accessible treatment option, particularly for those patients who cannot afford or do not need implant treatment. It is often one of the best solutions when the complete extraction of the remaining teeth is unavoidable. The denture is fitted immediately after the surgical clearance of teeth. It acts as a splint for helping with haemostasis, preventing trauma, and promoting wound healing. More importantly, an immediate denture can copy the characteristics of the existing dentition and establishes the vertical dimension of occlusion. It offers immediate replacement of the missing teeth, thereby avoiding a period of edentulism and social embarrassment. These treatments help relieve patient anxiety and bring about patient satisfaction. This study used a case report to illustrate the clinical procedures required for the construction of an immediate complete maxillary denture with good retention, support, stability, and aesthetics.Keywords: prosthodontics, rehabilitation, immediate complete denture, case report